Fostering Tactical Skills - David Hutama (Ardeth, 2022)
Assuring competencies in graduates from architecture school is a challenging task nowadays. The swift development of architectural-related technologies has staged an urgency for rethinking what the relevant competencies are. On the contrary, redefining competencies is unfavorable for architectural practices. Such circumstances put architectural education in an awkward position, especially as institutions are expected to produce future practicing architects; still, at the same time, graduates should be equipped with scholarly research tools. The former and the latter competencies are frequently incoherent.In this visual essay, I would like to argue that repositioning architectural education – in the form of what Michel de Certeau calls ‘tactics’ – is in line with the nature of design knowledge. In this way, students would have sufficient knowledge and skills to navigate the current situation and have no problem in the compliance with standardization.